PERFORMANCE OF INDIAN BANKS IN INDIAN FINANCIAL SYSTEM - DR. VIRENDER KOUNDAL (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Efficiency and profitability of the banking sector in India has assumed primal importance due to intense competition, greater customer demands and changing banking reforms. This study attempts to measure the relative performance of Indian banks. For this study, we have used public sector banks, old private sector banks, new private sector banks and foreign sector banks. We know that in the service sector, it is difficult to quantify the output because it is intangible. Hence different proxy indicators are used for measuring the productivity of the banking sector. Segmentation of the banking sector in India was done along the following basis: number of banks, offices, number of employees, business per employees, deposits per employee, advances per employee, bank assets size, non-performing assets, etc. Overall, the analysis supports the conclusion that foreign owned banks are on average most efficient and that new banks are more efficient that old ones. The public sector banks are not as profitable as other sectors are. In terms of size, the smaller banks are globally efficient, but large banks are locally efficient. It means that efficiency and profitability are interrelated. It is true that productivity is not the sole factor but it is an important factor which influence to profitability. The key to increasing profitability is increasing productivity. For this we have recommended some suggestions to tackle the challenges faced by the banks particularly public sector banks.